Dilemmas of neonatal burn management: A case report - Gabriel Allotey (Elsevier, 2019)
Neonatal burn injuries are rare in occurrence and commonly accidental. Neonates are high risk population due to their immature homeopathic and immune systems. Management of neonatal burn possess challenging difficulties as there are no clear guidelines regarding the care of neonatal burn victims as opposed to older children and adult.This is a case report of a 5 days old neonate who sustained full thickness burns to the lower limbs and left forearm when a light bulb on a ceiling exploded and caught fire burning her cover clothes. The baby was managed by fluid resuscitation, analgesics, antibiotics, exclusive breastfeeding and conservative wound care. Due to the fragile and thin nature of the neonatal skin, lack of ethical clearance to carry out allograft and financial constraint to procure a synthetic skin substitute or dermal analog, early excision and skin graft was suspended. Conservative wound care with Silver Sulfadiazine was employed. Measures were instituted to prevent wound contamination. The overall effect was longer period of hospitalization. The baby was on admission at the burns intensive care unit for forty one (41) days and was reviewed regularly. No complication was observed. She was moved to a low dependent area of care which signified that her condition was not critical. She was discharged a month later to come for wound dressing on out-patient basis. A referral was made to the physiotherapist to review for future scarring and contractures. Keywords: Neonate, Neonatal burn injury, Thermal burns, Full thickness, Nursing